MicroRNA-449c-5p inhibits osteogenic differentiation of human VICs through Smad4-mediated pathway - Rongjian Xu (Nature Portfolio, 2017)
Abstract Calcific aortic valve disease (CAVD) is the most common heart valve disorder, yet its mechanism remains poorly understood. Valve interstitial cells (VICs) are the prevalent cells in aortic valve and their osteogenic differentiation may be responsible for calcific nodule formation in CAVD pathogenesis. Emerging evidence shows microRNA (miRNA, or miR) can function as important regulators of many pathological processes, including osteogenic differentiation. Here, we aimed to explore the function of miR-449c-5p in CAVD pathogenesis. In this study, we demonstrated the role of miR-449c-5p in VICs osteogenesis. MiRNA microarray assay and qRT-PCR results revealed miR-449c-5p was significantly down-regulated in calcified aortic valves compared with non-calcified valves. MiR-449c-5p overexpression inhibited VICs osteogenic differentiation in vitro, whereas down-regulation of miR-449c-5p enhanced the process. Target prediction analysis and dual-luciferase reporter assay confirmed Smad4 was a direct target of miR-449c-5p. Furthermore, knockdown of Smad4 inhibited VICs osteogenic differentiation, similar to the effect observed in up-regulation miR-449c-5p. In addition, animal experiments proved indirectly miR-449c-5p could alleviate aortic valve calcification. Our data suggested miR-449c-5p could function as a new inhibitory regulator of VICs osteogenic differentiation, which may act by targeting Smad4. MiR-449c-5p may be a potential therapeutic target for CAVD.